Records of Cyathea spinulosa Wallich ex Hooker (Cyatheaceae) and Cycas pectinata Griff.(Cycadaceae) from the Churiya Hills of Eastern Nepal - Bhuju, Dinesh R.; Joshi, Giri P. (Nepal Journal of Science and Technology, 2010)
Nepal hosts 16 plant species of CITES appendix. The CITES appendix II includes Cyathea spp. (tree fern, Family Cyatheaceae) and the appendix III includes Cycas pectinata (Family Cycadaceae). During an ecological survey of Churiya hills of eastern Nepal, these two rare and endangered plants have been recorded in their natural habitats. The Churiya in eastern Nepal receives relatively high precipitation, and for its steep slopes with erodible poor soil, Churiya has very little to offer for agriculture and human settlement keeping the natural forest intact. However, the human population growth in the area has put pressure on the habitat and threatened the rare plants. Key words : Ecology; Forest; Fossil plants; Threatened species DOI: 10.3126/njst.v10i0.2827 Nepal Journal of Science and Technology Volume 10, 2009 December Page: 69-72